Subprime mortgages, foreclosures, and urban neighborhoods - Kristopher S. Gerardi; Paul S. Willen (Federal Reserve Bank of Atlanta, 2009)
This paper analyzes the impact of the subprime mortgage crisis on urban neighborhoods in Massachusetts. We explore the topic using a data set that matches race and income information from Home Mortgage Disclosure Act data with property-level, transaction data from Massachusetts Registry of Deeds offices. With these data, we show that much of the subprime lending in the state was concentrated in urban neighborhoods and that minority homeownerships created with subprime mortgages have proved exceptionally unstable in the face of rapid price declines. The evidence in Massachusetts suggests that subprime lending did not, as commonly believed, lead to a substantial increase in homeownership by minorities but instead generated turnover in properties owned by minority residents. Furthermore, we argue that the particularly dire foreclosure situation in urban neighborhoods actually makes it somewhat easier for policymakers to provide remedies.
Keywords: D11; D12; G21; 330; subprime; foreclosure; minority; homeownership; Finanzmarktkrise; Subprime-Hypothek; Zwangsvollstreckung; Wohneigentum; Stadt; Massachusetts